ANALISIS MINAT BELAJAR MAHASANTRIWATI SEMESTER Ⅲ MA’HAD ‘ALY MOHAMMAD NATSIR PUTRI KARTASURA PADA MATA KULIAH ‘ARABIYYAH BAINA YADAIK - Asma Husna Afifah; Zahrodin Fanani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the process of learning Arabic using the book ‘Arabiyyah Baina Yadaik, the learning interest of female students, and the factors influencing their interest in learning the topic of Mamnu’ Minash Sharf at Ma’had ‘Aly Mohammad Natsir Putri. The study employed a descriptive qualitative approach involving 10 third-semester female students selected through purposive sampling techniques. The data were collected through observation, questionnaires, and documentation. The results of the study indicate that the learning process was conducted systematically by integrating Arabic language instruction in the classroom with the habituation of using Arabic in the ma’had environment. The teaching methods applied included lectures, question-and-answer sessions, reading exercises, and hiwar (dialogue) practice, which supported the active participation of the students in the learning process. The students’ learning interest was categorized as relatively high, as reflected in their attention, enthusiasm, and active participation during the learning activities.The factors influencing learning interest consisted of internal and The results of the study indicate that the learning process was conducted systematically by integrating Arabic language instruction in the classroom with the habituation of using Arabic in the ma’had environment. The teaching methods applied included lectures, question-and-answer sessions, reading exercises, and hiwar (dialogue) practice, which supported the active participation of the students in the learning process. The students’ learning interest was categorized as relatively high, as reflected in their attention, enthusiasm, and active participation during the learning activities.